1999
DOI: 10.1097/00008483-199907000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Modification Program in Management of Patients With Coronary Artery Disease: The Clinical Experience in a Tertiary Care Hospital

Abstract: Multidisciplinary lifestyle modification programs addressing cardiovascular risk factors are known to have a significant impact upon cardiac risk factors in patients with coronary atherosclerosis. Data show that these changes can be accomplished in independent-living patients in a program offered through a routine cardiology service. However, compliance is an important issue in these self-regulated programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…In turn, the stress response of obese people has been shown to be exaggerated, which may further increase the risk of weight gain. Stress management has then been suggested as a weight control strategy to stop this vicious cycle [90] and, expectedly, lifestyle interventions targeting stress reduction have shown weight-control benefits [97]. Interestingly, the state of low physical activation appears to intensify the acute response to psychological stressors [92], and consistently sedentary lifestyles potentiate the stress-related health complications such as obesity, particularly visceral obesity [91, 95].…”
Section: Physical Exercise As a Buffer To The Deleterious Effects mentioning
confidence: 99%
“…In turn, the stress response of obese people has been shown to be exaggerated, which may further increase the risk of weight gain. Stress management has then been suggested as a weight control strategy to stop this vicious cycle [90] and, expectedly, lifestyle interventions targeting stress reduction have shown weight-control benefits [97]. Interestingly, the state of low physical activation appears to intensify the acute response to psychological stressors [92], and consistently sedentary lifestyles potentiate the stress-related health complications such as obesity, particularly visceral obesity [91, 95].…”
Section: Physical Exercise As a Buffer To The Deleterious Effects mentioning
confidence: 99%
“…Several studies have shown that weight loss (as part of a comprehensive lifestyle intervention) appears to be beneficial with respect to improvement in metabolic aberrations and a reduction in cardiac morbidity in obese and glucose-intolerant subjects at high risk of vascular events [8][9][10][11][12] . However, weight reduction and the long-term maintenance of lower body weight can be difficult to achieve, and very few obese patients maintain the shortterm weight losses achieved following dietary restriction [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Never smoked conclusions were drawn by Rutledge et al 15 in their two-year assessment of 43 men and women with coronary disease who adopted a risk factor modification program, when compared to 28 who abandoned the program, presenting decrease in total cholesterol and LDL-cholesterol as the result of dietary changes. In this case, the conditions were quite similar to those in the present study, as the patients were nor removed from their natural habitat, as in the case studied by Ornish et al, in which the individuals were confined to a hotel.…”
Section: Pre-program Smoking Statusmentioning
confidence: 98%